Shapiro’s Legality - Brand, Jeffrey (2015)
Scott Shapiro’s Legality provides at once a defense of analytical jurisprudence, an accessible introduction to it, and an important new positivist theory of law. Shapiro seeks to answer the main traditional questions of jurisprudence: “what is it about law that makes it law and not something else?” and “what necessarily follows from the fact that something is law?” His major innovation, building on Michael Bratman’s work, is to re-imagine H. L. A. Hart’s secondary rules, including his ultimate rule of recognition, as plans of a sort. Shapiro’s overarching goal, however, is to show that analytical jurisprudence has practical relevance for lawyers. I argue that his success is limited by his failure to present a coherent theory of how judges are morally permitted to rule, particularly in cases in which the law requires them to reach results that they consider to be unjust.
Keywords: Ronald Dworkin; Legal positivism; rule of recognition; plans; Michael Bratman; H. L. A. Hart; analytical jurisprudence